The gradient of Gurken, a long-range morphogen, is directly regulated by Cbl-mediated endocytosis. - Chang, W.L.; Liou, W.; Pen, H.C.; Chou, H.Y.; Chang, Y.W.; Li, W.H.; Chiang, W.; Pai, L.M. (Development, 2008)
The asymmetric localization of gurken mRNA and post-translational sorting mechanisms are responsible for the polar distribution of Gurken protein in Drosophila. However, endocytosis of Egfr, the receptor for Gurken in the follicle cells, also plays a role in shaping the extracellular gradient of the Gurken morphogen. Previously, we have found that mutation in the Cbl gene caused elevated Egfr signaling along the dorsoventral axis, and resulted in dorsalization phenotypes in embryos and egg shells. Here, we report that overexpression of the Cbl long isoform significantly changed Gurken distribution. Using an HRP-Gurken fusion protein, we demonstrate that internalization of the Gurken-Egfr complex depends on the activity of Cbl. Increased levels of CblL promote the internalization of this complex, leading to the reduction of free ligands. The Gurken-Egfr complex trafficks through the Rab5/Rab7 associated endocytic pathway to the lysosomal degradation compartment for signaling termination. We observe endocytic Gurken not only in the dorsal but also in the ventral follicle cells, which is, to our knowledge, the first visualization of Gurken on the ventral side of egg chambers. Our results show that Gurken travels towards the lateral/posterior of the egg chamber in the absence of Cbl, suggesting that Cbl actively regulates Gurken distribution through promoting endocytosis and subsequent degradation.